The Role of Supply Chain Management (SCM) in Maintaining Sino Competitive Advantage as a Global Exporter - Sande, Sara Julieta Luís Tomás; Sheng, Yu; Jaman, Barkat Ullah (APPS Publications, 2025)
This study work explores how the integration of supply chain management (SCM) and the efficiency of logistics help in sustaining China as an export country due to increasing cost of production, geopolitical unpredictability, and increasing global competitiveness. It also explores the mediation effects of the relationships between SCM integration, logistics efficiency, and export competitiveness of Chinese exporters by cost reduction. The research design is a quantitative, explanatory research design using survey research data collected on 300 Chinese export firms in four major industries, namely electronics, textiles, machinery, and consumer goods. The collected data were collected using online and face-to-face surveys conducted with both mid- and senior-level managers of major export centers (Shanghai, Guangzhou, and Shenzhen). The direct and mediating relationships between SCM integration, the efficiency of logistics, the reduction of costs, and export competitiveness were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that SCM integration, as well as logistics efficiency, has a direct effect of great magnitude and positive significance on the export competitiveness. Integration of SCM and logistic efficiency also leads to a significant fall in the cost of the operation. Nonetheless, cost reduction is neither directly related to export competitiveness nor does it mediate the relationship between SCM integration and export competitiveness. Conversely, cost reduction has a much stronger mediating effect on the relationship between logistics efficiency and export competitiveness, and this means that cost savings through logistics efforts are still a significant transmission mechanism. The paper contributes to the SCM and global business literature by proving the structural change in competitiveness among the exports in China, i.e., shifting more to direct value-creation potentials entrenched in the SCM integration and performance of logistics. It offers empirical data of rare firm-level in China, which dispels the traditional belief that cost reduction is the central mediator between the SCM practices and the export success.